Host identity shapes Endozoicomonas composition in coral microbiomes across depths and marine protected areas at Little Cayman Island - Madelaine L. Brown; Andrew J. Maritan; Gretchen Goodbody-Gringley; Matthew L. Doherty; Alex D. Chequer; Frank J. Stewart; Zoe A. Pratte (Coral Reefs, 2026)
The bacterial genus Endozoicomonas is prevalent and abundant in the microbiome of many corals, but the combination of environmental and host factors shaping its distribution remains uncertain. In this study, we used 16S rRNA gene sequencing to examine the distribution of Endozoicomonas across hard ( Porites astreoides , Montastraea cavernosa , Agaricia spp.) and soft coral ( Muricea spp., Gorgoniidae, Cladiellidae, Malacalcyonacea) microbiomes across a depth gradient from shallow (4.5 m) to upper mesophotic zones (36.6 m) at four sites around the Little Cayman Island, including two marine protected areas. Endozoicomonas was abundant across all coral microbiomes, with soft corals exhibiting near-total dominance (relative abundance range 0.1–99%, median 55.3%) by this genus and notable abundances (range 0–96%, median 22.2%) in hard corals. Endozoicomonas composition was strongly structured by coral host identity across sites and depths, with each coral type harboring two to four unique Endozoicomonas amplicon sequence variants. Site and depth also contributed to Endozoicomonas abundance in soft and hard corals, respectively, where relative abundances were highest at unprotected sites in soft corals and in shallow to mid photic zones in hard corals. These findings suggest that Endozoicomonas abundance is shaped by both coral host identity and local environmental conditions.